MENINGKATKAN HASIL BELAJAR IPA MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING - SUHAR SUHAR (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2022)
This study aims to improve science learning outcomes through the problem-based learning model for class IX C students at SMP Negeri 134 Jakarta in the second semester of the 2018/2019 academic year. This research uses action research method which is divided into two cycles, where each cycle consists of four stages, namely: 1) Planning, 2) Implementation, 3) Observation, and 4) Reflection. In this study, the researcher acted as a subject teacher in Class IX C at SMP Negeri 134 Jakarta. Based on the results of the study, it can be concluded that science learning outcomes can be improved through the Problem Based Learning Learning Model as evidenced by the student assessment that there is an increase in the first cycle with an average score of 76 and in the second cycle an average of 84. This learning model can be implemented by science teachers because can improve student learning outcomes and change students' thinking that science is less interesting to be more interesting. ABSTRAKPenelitian ini bertujuan untuk mengetahui efektifitas model Problem Based Learning dengan metode online dalam meningkatkan hasil belajar kimia tentang kimia karbon khususnya asam amino dan protein pada kelas XII MIPA 3 SMA Negeri 2 Bantul tahun pelajaran 2020/2021. Dalam penelitian ini data diambil dari observasi kedisiplinan (kehadiran siswa), keaktifan siswa dalam tanya jawab, tanggung jawab dalam pengumpulan tugas dan hasil tes, data ini dianalisis secara deskriptif kualitatif. Hasil penelitian menunjukkan bahwa dalam pembelajaran menggunakan model Problem Based Learning dengan metode online ini 94,12% siswa mencapai ketuntasan, 95,5 % siswa disiplin dalam kehadiran, 81,2 % siswa aktif dalam tanya jawab dan 100 % siswa bertanggungjawab dalam menyelesaikan tugasnya. Kedisiplinan, keaktifan serta tanggungjawab ini sangat membantu siswa dalam menguasai materi pelajaran sehingga mereka bisa mendapatkan hasil belajar yang tinggi.